HOMOGRAPHS BETWEEN INDONESIAN AND THAI: CONTRASTIVE ANALYSIS - Mukhlas, Moh.; Lestari, Oktavia Winda; Khoirunnisa, Krismonika; Aidha, Fakhriyyah Asmay; Butsaman, Wisaruta (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to describe the forms and expressions of understanding in Indonesian and Thai with a focus on homographs. The techniques used in this research are observation and note taking techniques. To achieve this goal, the listening method was used in data collection with note-taking techniques, namely observing, listening and recording vocabulary. Next, classify Indonesian vocabulary and Thai vocabulary. Next, to analyze Indonesian vocabulary and Thai vocabulary, this was done by comparing the similarities between the forms of expression and meaning of vocabulary in Indonesian with vocabulary in Thai and then classifying them. The data source was obtained through interactions between students in language learning in Thai students' classes and then compared with Indonesian. The research results show that there are two types of homographs, namely, the same meaning and pronunciation, and the same pronunciation and different meaning.